Applied tribology : bearing design and lubrication - Khonsari, Michael M.; Booser, E. Richard (Wiley, 2017)
'Applied Tribology' maintains a balance between the theory and application of the technology, giving particular emphasis to tribology in aerospace equipment, steam and gas turbines, motors and generators, transportation and marine equipment, and appliances. Insightful working knowledge of friction, lubrication, and wear in machinesApplications of tribology are widespread in industries ranging from aerospace, marine and automotive to power, process, petrochemical and construction. With world-renowned expert co-authors from academia and industry, Applied Tribology: Lubrication and Bearing Design, 3rd Edition provides a balance of application and theory with numerous illustrative examples. The book provides clear and up-to-date presentation of working principles of lubrication, friction and wear in vital mechanical components, such as bearings, seals and gears. The third edition has expanded coverage of friction and wear and contact mechanics with updated topics based on new developments in the field. Key features:Includes practical applications, homework problems and state-of-the-art references. Provides presentation of design procedure. Supplies clear and up-to-date information based on the authors' widely referenced books and over 500 archival papers in this field. Applied Tribology: Lubrication and Bearing Design, 3rd Edition provides a valuable and authoritative resource for mechanical engineering professionals working in a wide range of industries with machinery including turbines, compressors, motors, electrical appliances and electronic components. Senior and graduate students in mechanical engineering will also find it a useful text and reference.- Resumé vydavatel
Includes index.
Keywords: tribologie; tribology; elektronické knihy; monografie; electronic books; monographs